The Life of Ibn Surayj, Scientific Personality and His Place in Shafii Doctrine - Aydemir, Ramazan (Çukurova Üniversitesi, 2024)
After the death of the Prophet Muhammad (peace be upon him), several differences of opinion emerged among the Companions, and these differences gradually evolved into systematic schools of thought. One of these schools is the Shafi'i school, which was established under the leadership of Imam Shafi'i. Following the death of Imam Shafi'i, his first-generation students spread his jurisprudence through teaching and the works he authored. This initial period of the Shafi'i school facilitated the establishment and dissemination of its fundamental principles and practices. The second generation of Shafi'is expanded the reach of this teaching to different geographical regions, thus broadening the school's influence. The third generation of Shafi'i jurists, led by Ibn Surayj, systematized Shafi'i jurisprudence and made significant contributions to its institutionalization. After Imam Shafi'i, Ibn Surayj began the second compilation of the school, further deepening the details and principles of application of Shafi'i jurisprudence. Ibn Surayj's scholarly work is of great importance not only for understanding the intellectual atmosphere of his time but also for assessing his contributions to the development of the Shafi'i school. These efforts played a critical role in the instituti onalization and evolution of Shafi'i legal thought.

Hz. Peygamber’in (s.a.s.) vefatından sonra, sahabe arasında çeşitli görüş farklılıkları ortaya çıkmış ve bu farklılıklar zamanla sistemli mezheplere dönüşmüştür. Bu mezheplerden biri, Şâfiî mezhebi olup İmam Şâfiî'nin önderliğinde kurulmuştur. İmam Şâfiî'nin vefatının ardından, ilk nesil talebeleri, fıkhını dersler ve telif ettiği eserlerle yaymışlardır. Şâfiî mezhebinin bu ilk dönemi, mezhebin temel ilkelerinin ve uygulamalarının yerleşmesine ve yayılmasına olanak sağlamıştır. İkinci kuşak Şâfiîler, bu öğretimi farklı coğrafi bölgelere taşıyarak mezhebin etki alanını genişletmişlerdir. İbn Süreyc'in liderliğindeki üçüncü nesil Şâfiî fukaha ise, Şâfiî fıkhını daha sistemli bir hale getirmiş ve mezhebin kurumsallaşmasına büyük katkıda bulunmuştur. İbn Süreyc, İmam Şâfiî'den sonra mezhebin ikinci telifini başlatarak, Şâfiî fıkhının detaylarını ve uygulama esaslarını daha da derinleştirmiştir. İbn Süreyc'in ilmî çalışmaları, sadece o dönemin entelektüel atmosferini anlamak açısından değil, aynı zamanda Şâfiî mezhebinin gelişimine olan katkıları açısından da büyük bir öneme sahiptir. Bu çalışmalar, mezhebin kurumsallaşması ve fıkhî düşüncesinde kritik bir rol oynamıştır.
İBN SÜREYC’İN HAYATI, İLMÎ KİŞİLİĞİ VE ŞÂFİÎ MEZHEBİNDEKİ YERİ
Keywords: Islamic Law; İslam Hukuku